Diagnosis, therapy, and evidence : conundrums in modern American medicine - Grob, Gerald N., 1931-2015; Horwitz, Allan V. (Critical issues in health and medicine., 2010)
In Diagnosis, Therapy, and Evidence, Gerald N. Grob and Allan V. Horwitz employ historical and contemporary data and case studies, combining into one book a variety of medical and psychiatric conditions. They utilize case studies and examine tonsillectomy, cancer, heart disease, PTSD, anxiety, and depression, and identify differences between rhetoric and reality and the weaknesses in diagnosis and treatment.